(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Content and Language Integrated Learning (CLIL) has emerged as a significant pedagogical approach in bilingual education, combining the learning of content subjects with language development. This article explores the benefits of CLIL within bilingual educational settings, focusing on key methodological aspects that enhance both language proficiency and subject knowledge. Through a comprehensive literature review, this study identifies effective strategies employed in CLIL classrooms, examines the impact on student outcomes, and discusses the implications for educators. The findings suggest that CLIL not only improves language skills but also fosters critical thinking, cultural awareness, and engagement among learners.